Ekspresi Semantis Verba dan Pelibatan Argumen dalam Klausa Bahasa Bima - Made Sri Satyawati; Ketut Widya Purnawati; I Nyoman Kardana (Universitas Airlangga, 2019)
Bimanese language is an Austronesian, Malayo Polinesian Language (Arafik 2005). In 1986, Jonker conducted a research on this language. His reseach focused on sintactic structure of the language. Jonker’s analisis (1896) looked similar with Owens’ analisis (2000) that stated there are two common features of the Bimanese as one of the Austronesian language, they are affixing and compounding. With the base features, Owens considered that Bimanese at least has one of the features or even both features as well. His work focused on verb expression and bound arguments in Bimanese clauses. The two problems were analyzed based on Functional Lexical Grammar theory proposed by Kroeger (2005). The theory contains three sintactic aspects, such as functional structure, constituent structure, and argument structure. Data were collected through elicitation and observation method. Elicitation was applied to obtain spoken data while observation method was used to collect written data from texts. Both methods were supported by note taking technique and recording. The collected data were analyzed by substitution and immediate constituent technique. The result shows that Bimanese verbs can express their arguments syntactically by using verb semantic meaning and preposition like labo, kai, wea, and ba-. It was also found that the obligatory arguments in a clause are generally marked with the four markers.